Guided Imagery Therapy: An Approach to Improve Antepartum Quality of Life Among Women with Pregnancy-Induced Hypertension - Jasmine Jesy; Sadhana Adhyapak; Jaya John Varghese; S. Prema; Jamadhar Khrushid (Journal of Pharmacy and Bioallied Sciences)
Background: Pregnancy-induced hypertension (PIH) negatively affects the antepartum quality of life, necessitating complementary interventions to improve maternal well-being. This study evaluates the effectiveness of guided imagery therapy in enhancing the quality of life among women with PIH. Objectives: To assess the impact of guided imagery therapy on antepartum quality of life in women diagnosed with PIH. Methods: A quasi-experimental study was conducted with 60 participants assigned to either a study group (n=30) receiving guided imagery therapy or a control group (n=30) receiving standard care. Quality of life was measured using a validated scale before and after the intervention. Results: The study group showed a significant improvement in quality-of-life scores compared to the control group, indicating the positive effect of guided imagery therapy. Conclusion: Guided imagery therapy effectively enhances antepartum quality of life in women with PIH, supporting its integration as a complementary intervention in maternal care.